2021
DOI: 10.3389/fcell.2021.706755
|View full text |Cite
|
Sign up to set email alerts
|

Low-Intensity Exercise Modulates Gut Microbiota to Fight Against Radiation-Induced Gut Toxicity in Mouse Models

Abstract: Radiation-induced gastrointestinal (GI) tract toxicity halts radiotherapy and degrades the prognosis of cancer patients. Physical activity defined as “any bodily movement produced by skeletal muscle that requires energy expenditure” is a beneficial lifestyle modification for health. Here, we investigate whether walking, a low-intensity form of exercise, could alleviate intestinal radiation injury. Short-term (15 days) walking protected against radiation-induced GI tract toxicity in both male and female mice, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…Although our previous study identified the protective effect of A. muciniphila against intestinal radiation injuries 26 , some individuals always showed an unsatisfactory response (Supplementary Fig. 9 ).…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Although our previous study identified the protective effect of A. muciniphila against intestinal radiation injuries 26 , some individuals always showed an unsatisfactory response (Supplementary Fig. 9 ).…”
Section: Resultsmentioning
confidence: 87%
“…Akkermansia muciniphila ( A. muciniphila ) is a potential probiotic and has been proven to fight against colorectal cancer and many metabolic diseases 24 , 25 . In our previous study, although A. muciniphila alleviated intestinal radiation injuries in mouse models, some individuals always experienced unsatisfactory therapeutic effects 26 . Whether the colonization of probiotics dictates their therapeutic efficacy and how monobacterial preparation optimizes the gut microhabitats remain poorly understood.…”
Section: Introductionmentioning
confidence: 95%
“…Ionizing radiation has been used in many fields, like chest X-ray, computed tomography (CT) and radiation therapy. Radiotherapy, as the most effective cytotoxic treatment, is used to cure more than 50% of cancer patients throughout the world . Nevertheless, people subjected to ionizing radiation, such as radiology technologists, radiologists and particularly cancer patients, always develop a series of clinical complications, including toxicity in the bone marrow (hematopoietic syndrome) and GI symptoms. ,, A previous study demonstrated that the small intestine, which is the largest organ in the body and exhibits a higher sensitivity to ionizing radiation, is the major site of damage during irradiation. , Despite having the highest self-renewal rate of the intestinal epithelium, acute radiation injury of intestine may facilitate mucosal epithelium injury, leading to malabsorption, diarrhea, bacterial influx, sepsis, and even death. , Hence, radiation-induced gastrointestinal damage, especially small intestine injury, is a severe problem that needs to be effectively treated for people suffering from IR exposure.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Next, we aimed to screen for the gut microbe which was able to mitigate intestinal radiation injury in high-ranking mice. For the monoassociation study, Lactobacillus murinus ( L. murinus ) was selected due to (i) its recognition as a classic probiotic [ 35 , 36 ], (ii) its presence as the dominant gut strain in both Dom and Sub mice ( Figure 1 F and Figure 5 A,B), (iii) its significant reduction in frequency in Dom mice after TAI ( Figure S5A ). We clarified the radioprotective function of L. murinus in mice without social hierarchy, which have been most frequently used in traditional research ( Figure 5 C).…”
Section: Resultsmentioning
confidence: 99%